HspB5 Activates a Neuroprotective Glial Cell Response in Experimental Tauopathy - Hampton, David W.; Amor, Sandra; Story, David; Torvell, Megan; Bsibsi, Malika; van Noort, Johannes M.; Chandran, Siddarthan (Frontiers in Neuroscience, 2020)
Progressive neuronal death during tauopathies is associated with aggregation of modified, truncated or mutant forms of tau protein. Such aggregates are neurotoxic, promote spreading of tau aggregation, and trigger release of pro-inflammatory factors by glial cells. Counteracting such pathogenic effects of tau by simultaneously inhibiting protein aggregation as well as pro-inflammatory glial cell responses would be of significant therapeutic interest. Here, we examined the use of the small heat-shock protein HspB5 for this purpose. As a molecular chaperone, HspB5 counteracts aggregation of a wide range of abnormal proteins. As a TLR2 agonist, it selectively activates protective responses by CD14-expressing myeloid cells including microglia. We show that intracerebral infusion of HspB5 in transgenic mice with selective neuronal expression of mutant human P301S tau has significant neuroprotective effects in the superficial, frontal cortical layers. Underlying these effects at least in part, HspB5 induces several potent neuroprotective mediators in both astrocytes and microglia including neurotrophic factors and increased potential for removal of glutamate. Together, these findings highlight the potentially broad therapeutic potential of HspB5 in neurodegenerative proteinopathies.